2009
DOI: 10.1097/mbc.0b013e32832dc327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidosis, alkalosis, hyperthermia and hypothermia on haemostasis: results of point of care testing with the thromboelastography analyser

Abstract: In this study we assessed the effects of changes in pH, temperature, and their combination in whole blood on thromboelastographic variables. Blood was collected from six healthy volunteers. Thromboelastograph (TEG series 5000; Haemoscope Corporation, Illinois, USA) channels were set at temperatures of 32, 37, and 39 degrees C and each was filled with artificially acidified, alkalified, and neutral blood, respectively. Acidification (pH 6.95) significantly impairs thromboelastographic variables reaction time r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
1
33
1
1
Order By: Relevance
“…When coagulation is assessed using thromboelastometry or thromboelastography, hypothermia prolongs the coagulation time and clot formation time in whole blood. [8][9][10] In animal models, platelet counts fall significantly during deep hypothermia. This is believed to be due to a reversible sequestration of platelets in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…When coagulation is assessed using thromboelastometry or thromboelastography, hypothermia prolongs the coagulation time and clot formation time in whole blood. [8][9][10] In animal models, platelet counts fall significantly during deep hypothermia. This is believed to be due to a reversible sequestration of platelets in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…12 Other studies focused solely on pH-induced coagulation alteration. 13,14 However, no attempts have combined both study of acidemia and blood components to fully evaluate the possible contributions to ATC, particularly as measured by TEG.…”
mentioning
confidence: 99%
“…Hypothermia and acidosis are common complications in severely injured patients [1,2]. The negative impact of these conditions on coagulation resulting in coagulopathy has been well described [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia and acidosis are common complications in severely injured patients [1,2]. The negative impact of these conditions on coagulation resulting in coagulopathy has been well described [3][4][5][6][7][8][9].Desmopressin is a synthetic analogue of vasopressin (1-deamino-8-D-aginine vasopressin, DDAVP). Beside its first indication for treatment of cranial diabetes insipidus, it has become the treatment of choice for von Willebrand disease (Type I) and mild haemophilia A after it was shown that DDAVP leads to increased levels of coagulation factor (F) VIII, von Willebrand factor (vWF), and tissue plasminogen activator [10].…”
mentioning
confidence: 99%